Defining and Measuring Professionalism in Professions of Service Sector. - Hiba Khan; Mavra Khan (SEISENSE (PRIVATE) LIMITED, 2018)
The purpose of this paper is intended to measure the degree of professionalism in the professions like doctors, professors, lawyers, librarians, and advertisers. The study will measure the level of professionalism among them on the base of which their expectations for outcomes in the respective fields can be denied or honored. Moreover, the study will identify problem areas in these professions and opportunities for improving the quality of professional’s work. This study attempts to measure professional’s individual attributes by using questionnaire developed by William Snizek in 1972. This tool measures five factors of professionalism: organization as major referent, belief in public service, belief in self-regulation, sense of calling to the field and autonomy. Professionalism will be measured by calculating means of each factor and collective mean of factors for each profession. The study suggest that all under study professions have professionalism in them but there is room for improvement as well